Ownership dynamics around IFRS adoption: emerging markets context. Issue 1 (5th February 2018) - Hessayri, Manel; Saihi, Malek
Abstract : Purpose: The purpose of this paper is to analyze the firm's capital market benefits in a high-quality information setting. More specifically, the authors address the question of whether the commonly documented IFRS benefits are capable of influencing inducing shareholders to increase their equity investment in adopting firms. Design/methodology/approach: This study is performed on publicly listed firms in three emerging countries, namely, Morocco, South Africa and Turkey. The design of the ownership database allows a panel analysis for the years 2001 through 2011. The trend approach is suitable to account for concurrent effects that are unrelated to financial reporting while controlling for time-lasting behavior of investors. Overall, a minimum of four-year periods before and after the IFRS adoption date are warranted. Findings: Overall, the findings support evidence of increases in equity holdings following a firm's IFRS adoption. More specifically, institutional investors and institutional blockholders (both domestic and foreign) invest more heavily in the stocks of the firms that have committed to IFRS. By contrast, the authors fail to report evidence for ownership by blockholders and controlling shareholders. Practical implications: The current empirical work should be of value to international investors, policy makers and market authorities. As for international investors facing reduced information disadvantage and comparable financial information across worldwide markets, they will find it easier to select and invest in value-creating stocks. This study may be useful for policy makers in acquiring a clear view of advantages, challenges and relevance of IFRS adoption to emerging markets. In particular, this study contributes to an understanding of potential capital market consequences of IFRS adoption. Furthermore, market authorities should be aware of the importance of institutional framework to enhance IFRS implementation and usage. Originality/value: This work contributes to the ongoing empirical research on the intended capital market benefits of IFRS. The authors provide deeper insight into shareholdings changes of a number of key investors in a context where supply and demand of information are stained with asymmetry and mostly, influenced by differences in accounting practices. A major contribution of this study is the use of a methodological approach that outperforms commonly used approaches in the way how it considers concurrent events (compared to the shift specification) and time-lasting investor behavior (compared to the difference-in-differences analysis).